PENGARUH KETELADANAN GURU TERHADAP AKHLAK PESERTA DIDIK KELAS IX MTS AS’ADIYAH PUTERI 1 SENGKANG KABUPATEN WAJO - Amri, Muhammad; Assad, Andi Baso Muammar (Inspiratif Pendidikan, 2020)
The results showed that the influence of teacher exemplary behavior on the morals of grade IX students of MTs As’adiyah Puteri 1 Sengkang, Wajo Regency was very influential. The results of the descriptive analysis of the teacher’s example of the morals of class IX MTs As’adiyah students, taking into account 36 students as samples, 17 people or 47.22% of respondents were in the excellent category (SS) from the aspect of visual activity, 11 people or 36 , 11% of respondents were in the good category (S) writing activity, 5 people or 13.8% of respondents were in the unfavorable category (ST) from the aspect of oral activity, 3 people or 8.5% of respondents who were in the no category both (STS) in terms of motor activity. This illustrates that the teacher’s example of the morals of grade IX MTs As’adiyah Puteri 1 Sengkang students in Wajo Regency is in the category of strongly agree (SS) 47.22% of the aspects of writing activities.